Contactless power transfer system for sealed lead acid battery charging. Issue 1 (29th November 2017) - Rituraj, Gautam; Kushwaha, Brijesh Kumar; Kumar, Praveen
Abstract : In this paper, an experimental study is carried out while charging the sealed lead acid battery bank using a series-parallel (SP) compensated contactless power transfer (CPT) system. Constant current (CC) and constant voltage (CV) modes are used for charging the battery bank. An expression of optimum operating frequency is derived to maintain the maximum compensated coil efficiency throughout the load variation in charging process. An experimental setup of SP compensated CPT system is built for charging the battery bank. The variation of compensated coil efficiency and the load phase angle with respect to different operating frequencies in CC and CV modes is verified with the measurement. Based on the analysis, the control parameters are identified.